1996
DOI: 10.1007/bf00180324
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, massive and unphysiological breast enlargement

Abstract: Two cases of gigantomastia are presented, one is non-gravid and the other occurred during pregnancy. This is probably m o r e c o m m o n than has been reported but the cause remains unknown. The medical and surgical treatment of the disorder is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 70 publications
(185 reference statements)
0
5
0
Order By: Relevance
“…Other forms of BDA include polythelia (extra nipple), polymastia (extra breast), aplasia (absence of breast), hypomastia (underdeveloped breast), and tubular breast (breast with a tube-like shape) [12]. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other forms of BDA include polythelia (extra nipple), polymastia (extra breast), aplasia (absence of breast), hypomastia (underdeveloped breast), and tubular breast (breast with a tube-like shape) [12]. …”
mentioning
confidence: 99%
“…A diagnosis is made when an adolescent’s breasts grow rapidly and achieve great weight, usually soon after her first menstrual period [ 3 ]. Other forms of BDA include polythelia (extra nipple), polymastia (extra breast), aplasia (absence of breast), hypomastia (underdeveloped breast), and tubular breast (breast with a tube-like shape) [ 12 ].…”
mentioning
confidence: 99%
“…Ben Meir et al 11 described their experience of mastectomy and reconstruction using implants and a free nipple graft, with localization of the surgical scar at the meridian of the breast, which resulted in an inferior aesthetic result. Ohlsen et al 12 reported breast reduction and banking of the nipples followed by mastectomy with delayed reconstruction, and the nipples were replaced in the same stage. In our patient, we chose to perform bilateral mastectomy with delayed breast reconstruction and a free nippleareola complex graft.…”
Section: Discussionmentioning
confidence: 99%
“…Ohlsen et al. 12 reported breast reduction and banking of the nipples followed by mastectomy with delayed reconstruction, and the nipples were replaced in the same stage. In our patient, we chose to perform bilateral mastectomy with delayed breast reconstruction and a free nipple–areola complex graft.…”
Section: Discussionmentioning
confidence: 99%
“…Sagging of the breast can occur at various stages of women's life like postpartum and lactation, after gaining weight, menopause or at any age. 1 Many women are genetically predisposed for development of large breast, whose size increase either by weight gain or pregnancy. Rarely, young women can develop massive and oversized breasts called virginal mammary hypertrophy.…”
Section: Introductionmentioning
confidence: 99%